King Lear - Shakespeare, William 1564-1616.; Bain, Elspeth; Morris, Jonathan, 1954-; Smith, Robert, 1954 Apr. 24- (New York : Cambridge University Press, 2000)
An edition of Shakespeare's tragedy, including discussion of its plot, themes, characters, language, production, and author.
Keywords: Shakespeare, William, -- 1564-1616. -- Problems, exercises, etc; Shakespeare, William, -- 1564-1616.; Lear, King (Legendary character) -- Drama; Young adult drama, English; Inheritance and succession -- Drama; Fathers and daughters -- Drama; Kings and rulers -- Drama; Aging parents -- Drama; Britons -- Drama; Lear, King (Legendary character) -- Drama; Plays